A Cannabinoid Receptor Type 1 (CB1R) Agonist Enhances the Developmental Neurotoxicity of Acetaminophen (Paracetamol). (25th August 2018) - Philippot, Gaëtan; Hallgren, Stefan; Gordh, Torsten; Fredriksson, Anders; Fredriksson, Robert; Viberg, Henrik
Abstract: Acetaminophen (AAP; also known as paracetamol) is the most used and only recommended analgesic and antipyretic among pregnant women and young children. However, recent findings in both humans and rodents suggest a link between developmental exposure to AAP and adverse neurobehavioral effects later in life. We hypothesized that the cannabinoid receptor type 1 (CB1R) may be involved in the developmental neurotoxicity of AAP, owing to its interaction with the endocannabinoid system. Here we test if CB1R agonist WIN 55 212-2 (WIN) and AAP can interact when exposure occurs during a neurodevelopmental stage known for increased growth rate and for its vulnerability to AAP exposure. We exposed male NMRI mice on postnatal day 10 to different combinations of AAP and WIN. Adult mice, neonatally co-exposed to AAP and WIN, displayed a significant lack of habituation in the spontaneous behavior test, when compared with controls and single agent exposed mice. These adult adverse effects may at least in part be explained by a reduction of transcript levels of hippocampal synaptophysin ( Syp ) and tropomyosin receptor kinase B ( Trkb ), and cerebral cortical fatty acid amide hydroxylase ( Faah ), 24 h after exposure. These findings are consistent with our hypothesis that AAP and WIN can interact when exposure occurs during early postnatal brain development in mice. Assuming our results are relevant for humans, they raise concerns on AAP safety because it is the only recommended analgesic and antipyretic during pregnancy and early life.